The Ideal Result What It Is and How to Achieve It - Hipple, Jack. (Springer New York : Imprint: Springer, 2012)
The TRIZ Inventive Problem Solving Process is a left-brained, highly creative method of problem solving which uses a basic algorithm developed through the study of millions of patents. Unlike psychological tools, which rely on sorting through hundreds of ideas in order to find the valuable few, TRIZ rigorously defines the problem and helps identify existing inventive principles that have helped solve other problems of the same class. It is also an invaluable aid for strategic business planning. The Ideal Result introduces the TRIZ Inventive Problem Solving Process in a way that allows readers to make immediate use of its most basic concepts. This book reviews the basic TRIZ algorithm tools, provides templates for analyzing your own difficult problems, and helps establish mental frameworks for finding your own solutions.